A variation on N? ward continuity - Cakalli, Huseyin; Et, Mikail; Sengul, Hacer (Walter de Gruyter Gmbh, 2020)
The main purpose of this paper is to introduce the concept of strongly ideal lacunary quasi-Cauchyness of sequences of real numbers. Strongly ideal lacunary ward continuity is also investigated. Interesting results are obtained.
Keywords: N-theta convergence; summability; continuity